Effects of filler-rubber interaction on dynamic mechanical properties and reinforcement of NR vulcanisates - Han J J; Guo W H; He X L; Wu C F (Plastics, Rubber and Composites, 2007)
DL
Keywords: Carbon black; Dynamic mechanical properties; Filler-rubber interaction; Modified carbon black; NR; Reinforcement; Stress-strain behaviour